HOPE FAMILY EVALUATION PROGRAM (PKH) - Septi Ayuna Hendra Liza; Evi Lorita; Yusuarsono Yusuarsono; Bando Amin C Kader (Perkumpulan Dosen Muda (PDM) Bengkulu, 2020)
PKH is a program launched by the government in the context of accelerating poverty reduction while at the same time improving the quality of human resources, especially in the very poor community groups throughout Indonesia. This program is specialized in two components, namely education and health. However, the program which is expected to create a quality of life for the poor, especially in the field of education and health, still has problems in implementing it in the field. The problem is that in practice there are still things that are not in accordance with the procedures that apply to the PKH general manual. The first problem is the uneven number of poor people who get aid funds from PKH. To find out the results of the 2019 program, that is by evaluating using six indicators. Through this type of qualitative research with descriptive research type, the researcher determines that this informant consists of key informants and key informants. Data collection techniques in this study used observation, interview and documentation techniques. This study aims to determine the results of the implementation of the PKH in Batu Raja Village, Pondok Kubang Sub-District, Central Bengkulu Regency by evaluating the implementation of the program in 2019. From the research and analysis of data conducted, it shows that the implementation of the program has run effectively. This is based on evaluation indicators done by the researcher.